PENGARUH PROFITABILITAS DAN LEVERAGE DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI TERHADAP MANAJEMEN LABA: THE EFFECT OF PROBABILITY AND LEVERAGE WITH GOOD CORPORATE GOVERNANCE AS MODERATORS ON EARNINGS MANAGEMENT - Alya Maulidina Putri; Kamaliah Kamaliah; Nurul Badriyah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2022)
This study aims to find empirical evidence related to the effect of Probability and Leverage with Good Corporate Governance as Moderators on Earnings Management on Infrastructure, Utilities, and Transportation Companies, Listed on the IDX for the 2018-2020 period. The population of this study is Infrastructure, Utilities, and Transportation Companies, Listed on the IDX for the 2018-2020. The sample of this study was selected using the purposive sampling method, the determination of the sample had been determined in advance based on the criteria. Hypothesis testing is done with the help of statistical test tools pls. The results of this study indicate that profitability has no effect on earnings management, leverage has an effect on earnings management, institutional ownership cannot moderate the effect of profitability and leverage on earnings management, managerial ownership can moderate the effect of leverage on earnings management but cannot moderate the effect of profitability on earnings management.